A Bizarre, Unexplained, and Progressive External Rotation of the Shoulder as a Presentation of a Metastatic Deposit in the Rotator Cuff - Sherif El-Tawil; Aditya Prinja; Jeremy Stanton (Case Reports in Orthopedics)
We describe the first reported case of a tumour deposit within the rotator cuff presenting as a bizarre, progressive, and fixed external rotation deformity of the shoulder. It is also the first reported case to our knowledge of an oesophageal primary metastasising to the rotator cuff.